Estimation of Surface Runoff Using SCS-CN Remote Sensing and GIS in Sanjab Watershed - Mujeeb, Mujeebullah; Hushmand, Shafiullah (Journal of Natural Sciences – Kabul University, 2026)
This study estimates surface runoff in the Sanjab watershed, located in Herat, Afghanistan, using remote sensing and GIS. Accurate runoff prediction is vital for hydro-technical project planning and watershed management, and the curve number (SCS-CN) method is a widely used technique based on soil and land-use data. The watershed covers 181 km², and data from 2012 to 2021 were analyzed. Results showed the peak surface runoff in 2019 at approximately 17.3 million cubic meters, while the lowest was in 2014 at approximately 9.06 million cubic meters. The average annual runoff was around 12.7 million cubic meters. The area was selected because plans to develop pistachio orchards depended on the available surface water from the Sanjab River, making accurate runoff assessment essential for effective water management and irrigation planning.